TIKTOK : MEMAHAMI DINAMIKA KONTEN ISLAMI DALAM ERA DIGITAL - Caniago, Fauzi; Juhridin, Juhridin (LPPM Politeknik Pajajaran ICB, 2024)
TikTok features Islamic content that allows audiences to watch it anytime and anywhere. This demonstrates that TikTok can be utilized as a diverse source of information, with some people using it for entertainment, promoting products, or engaging in da'wah. The aim of this study is to explore the characteristics of Islamic content on TikTok and its impact on users. The research method employs a qualitative descriptive approach, aiming to examine ongoing or natural phenomena.The findings indicate that TikTok has the ability to foster audience interaction through comments, challenges, or Q&A sessions, which is a distinctive feature of Islamic content. This interaction creates a strong sense of community among users who share Islamic values. Moreover, the demand for Islamic content on TikTok varies; some participants watch it to learn academic-related topics, while others view Islamic content to enhance their knowledge of Islam.